2021
DOI: 10.46542/pe.2020.202.136144
|View full text |Cite
|
Sign up to set email alerts
|

An online international pharmacy summer course during the COVID-19 pandemic

Abstract: The University of Southern California School of Pharmacy has offered a residential summer course for international undergraduate pharmacy students for many years, with a focus on clinical therapeutics. In 2020, the COVID-19 pandemic made it impossible to offer the on-campus course. After some discussion, the course was moved online, with the goals of maintaining links with international partners and providing students with a virtual study abroad experience. This article describes the planning and implementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Therefore, educator could cooperate with technological support service in educational institution to improve the sufficient program quality. Moreover, in the exchange program, synchronous classes could be challenging due to time differences and thus, program session and assignments should be carefully arranged [ 6 ]. In our program, the time difference was two hours, so it was not difficult to adjust; however, the program was conducted for three months long.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, educator could cooperate with technological support service in educational institution to improve the sufficient program quality. Moreover, in the exchange program, synchronous classes could be challenging due to time differences and thus, program session and assignments should be carefully arranged [ 6 ]. In our program, the time difference was two hours, so it was not difficult to adjust; however, the program was conducted for three months long.…”
Section: Discussionmentioning
confidence: 99%
“…In the medical educational field, there are a few reports of online international programs such as virtually visiting a medical institution in another country [ 4 , 5 ]. However, there are few reports of international exchange programs in which students participate from two or more universities and conduct activities together for several weeks [ 6 , 7 ]. To the best of our knowledge, there is no report promoting a program with interactive communication for a period of several months.…”
Section: Introductionmentioning
confidence: 99%
“…The survey data (Q4-Q6) indicated that >70% of the course assistants developed more interest in pursuing international learning opportunities. This is an important goal in the diversification of career opportunities for PharmD students, and one that has previously been shown to be under-utilized in schools of pharmacy (Kim et al, 2020). There is an increasing emphasis on the internationalization of education, healthcare, and industry, and exposure of students to these areas is important for career development (Kim et al, 2022a(Kim et al, , 2022b.…”
Section: Internationalizationmentioning
confidence: 99%
“…Mentoring of course assistants did not end with the completion of the program. Including our description of the earlier ISSP 2020 program (Kim et al., 2020), scholarship from the ISSPs has involved publications (Kim et al., 2020) and posters (Kim et al., 2022a; Goldenberg et al., 2021; Mojab et al., 2021) that have included 15 authorships for 10 different course assistants. The current article extends this scholarship for two‐course assistants.…”
Section: Post‐program Effectsmentioning
confidence: 99%
“…[5][6][7] There are some reports of international exchange programs in which students from two or more universities participate in activities together for several weeks. [8][9][10] These studies reported that well-organized and structural virtual programs could contribute to fostering globally competent medical professional students and give the opportunity for international experience to students from various backgrounds. However, those programs' evaluations in the reports were based on the students' feedback after joining the program to report and describe how participating students felt those experiences.…”
Section: Introductionmentioning
confidence: 99%